Courageous Practice: Tales from Reflexive Supervision - Paré, David; Audet, Cristelle; Bailey, Jackie; Caputo, Arcangelo; Hatch, Kevin; Wong-Wylie, Gina (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper explores a collaborative approach to counsellor supervision using a reflecting process. The first author, who acted as "supervisor" to the other contributors in a graduate level family therapy practicum, describes the theoretical context of the work, and details his experience of the supervisory role. The remaining authors, who acted as "supervisees", provide anecdotal accounts of their experience with the reflecting supervision process. The central focus is on the manner in which a reflexive orientation to supervision diminishes defensive postures on the part of participants and facilitates constructive learning.